2017
DOI: 10.1038/s41598-017-01983-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of metabolic status on the incidence of psoriasis: a Korean nationwide cohort study

Abstract: Growing evidence suggests that obesity is a risk factor for incident psoriasis. This study was aimed to evaluate the association of obesity and metabolic status with the incidence of psoriasis. A total of 418,057 adults were followed-up using a nationwide prospective cohort study in Korea. Participants were stratified based on the body mass index categories and metabolic condition. During the follow-up visit, 11054 (2.6%) cases were found to have psoriasis. Diabetes, hypertension, hyperlipidemia, and obesity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 43 publications
0
29
1
Order By: Relevance
“…In addition, a nested case–control study from the UK General Practice Research Database found an increase in psoriatic risk in obese patients of approximately 30% . Furthermore, a previous nationwide prospective cohort study in Korea demonstrated that BMI and metabolic status increased the risk of psoriasis . A meta‐analysis of prospective studies suggested that higher BMI and WC resulted in 19% and 24% increases in relative risk of psoriasis, respectively .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, a nested case–control study from the UK General Practice Research Database found an increase in psoriatic risk in obese patients of approximately 30% . Furthermore, a previous nationwide prospective cohort study in Korea demonstrated that BMI and metabolic status increased the risk of psoriasis . A meta‐analysis of prospective studies suggested that higher BMI and WC resulted in 19% and 24% increases in relative risk of psoriasis, respectively .…”
Section: Discussionmentioning
confidence: 98%
“…In obese individuals, saturated fatty acid overflow causes insulin resistance and activates inflammatory pathways . Inflammatory fatty tissue induces low‐grade systemic inflammation, which causes insulin resistance and endothelial dysfunction by releasing pro‐inflammatory cytokines and chemokines, including TNF‐α, IL‐1β, IL‐6, CCL2, CCL3, CXCL8 and leptins . The inflammatory environment caused by obesity plays a crucial role in triggering the onset of psoriasis, in which Th1 and Th17 lymphocytes play key roles .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors such as HTN, long treatment duration, and high cumulative doses of CsA were not associated with increased SCr levels. As psoriasis has been associated with a high incidence of metabolic diseases including HTN (Kim et al, 2017;Wan et al, 2018), the effects of these diseases on nephrotoxicity during the CsA treatment has important clinical implications. However, a significant association between HTN and nephrotoxicity was not revealed in our study, although a positive correlation between HTN and changes in the SCr levels in the first course of treatment was noted.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with psoriasis who are treated with CsA, nephrotoxicity is associated with longer term administration, a larger cumulative dose, and a higher daily dose (Coresh et al, 2001). Other risk factors include older age, male sex, obesity, hypertension (HTN), diabetes mellitus (DM), and concomitant use of nephrotoxic drugs (Colombo, Cassano, Bellia, & Vena, 2013;El-Bassossy & Eid, 2018;Kim et al, 2017;Maza et al, 2011;Rodier, Ribstein, Parer-Richard, & Mimran, 1991;Wan et al, 2018). Although intermittent treatment with CsA with 12-week courses has been generally recommended, there is still controversy regarding the optimal treatment strategy to prevent CsA nephrotoxicity (Colombo et al, 2013;Nast et al, 2015).…”
mentioning
confidence: 99%